Appreciation of the informed consent procedure in a randomised trial of decompressive surgery for space occupying hemispheric infarction. Issue 10 (30th March 2007) - Hofmeijer, J; Amelink, G J; den Hertog, H M; Algra, A; Kappelle, L J; van der Worp, H B; ,
Abstract : Background and aim: As non-randomised studies have suggested that surgical decompression may reduce mortality in patients with space occupying hemispheric infarction, randomisation may be considered unethical in controlled trials testing this treatment strategy. We studied differences in recall of information and in appreciation of the informed consent procedure between representatives included in the Hemicraniectomy After Middle cerebral artery infarction with Life-threatening Edema Trial (HAMLET) and representatives of patients participating in the randomised trial of Paracetamol (Acetaminophen) In Stroke (PAIS). Methods: 1 year after study inclusion, we contacted 30 consecutive representatives who had given informed consent for participation of their relative in HAMLET, and 30 for PAIS. Recall of trial details and appreciation of the informed consent procedure were investigated using standardised questionnaires and compared between the two groups. Results: All 30 PAIS representatives and 28 HAMLET representatives were interviewed. Participation of their relative in a clinical trial was remembered by 86% of HAMLET and 40% of PAIS representatives (p<0.001). HAMLET representatives remembered more trial details (effect of the treatment under study (61% vs 3%, p<0.001); randomised treatment allocation (71% vs 0%, p<0.001)). With respect to appreciation of the informed consent procedure, we found no differences between the groups: in each trial, four representatives (14% vs 13%) had considered the question of randomisation unacceptable. Conclusions: Participation of patients in a randomised controlled trial of surgical decompression for space occupying infarction is generally considered acceptable by their representatives, and recall of trial details is better than in a trial in which less vital issues are at stake.